2017
DOI: 10.1634/theoncologist.2017-0297
|View full text |Cite
|
Sign up to set email alerts
|

A Systematic Review of Health-Related Quality of Life Reporting in Ovarian Cancer Phase III Clinical Trials: Room to Improve

Abstract: The impact of treatment on quality of life (QOL) is an important consideration in patients with ovarian cancer for whom treatment is often given with palliative intent. Both the disease and treatment impact a patient's QOL and require careful evaluation in clinical trials. Matching the QOL questions to the patient population of interest is critical. Similar rigor to that used to assess progression-based endpoints is essential to guide clinical decisions. This systematic review demonstrated that although the in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
42
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(44 citation statements)
references
References 77 publications
1
42
1
Order By: Relevance
“…Given the potential chronicity of EOC, patients may experience a multitude of relapses and treatment-related adverse events (AE) that can impact quality of life (QOL). Efforts are on-going to integrate this endpoint into clinical trials and design studies in recurrent disease where the patient reported outcomes (PRO) are major endpoints 133 . At the time of recurrence, the goal of treatment is to control the disease and maintain QOL.…”
Section: Quality Of Life -Symptom Managementmentioning
confidence: 99%
“…Given the potential chronicity of EOC, patients may experience a multitude of relapses and treatment-related adverse events (AE) that can impact quality of life (QOL). Efforts are on-going to integrate this endpoint into clinical trials and design studies in recurrent disease where the patient reported outcomes (PRO) are major endpoints 133 . At the time of recurrence, the goal of treatment is to control the disease and maintain QOL.…”
Section: Quality Of Life -Symptom Managementmentioning
confidence: 99%
“…41 Although PRO data after disease progression is reached can be useful to assess the impact of treatments over time, a recent review of ovarian cancer clinical trials showed that none of the 35 phase 3 studies reviewed reported PRO findings after disease progression. 42 Missing values, attributable to death, dropouts, and patients being too ill to provide data, may be addressed by performing sensitivity analyses. Nevertheless, missing values caused by administrative errors, which generally arise when the PRO assessments are for exploratory endpoints (which may lack priority during study planning and conduct), may be difficult to address in analysis.…”
Section: Missing Datamentioning
confidence: 99%
“…The integration of patient-reported outcomes into clinical trials may provide greater insight into regimen tolerability, patients' symptom burden, and the implications of AEs beyond the CTCAE grading by clinicians. 16 A recent report by Henon et al 13 showed that patients' most feared AEs, which they deemed intolerable even when they were low grade (grade 1 or 2), were gastrointestinal and neurological toxicities as well as personality changes; these AEs were different from physicians' most feared toxicities and the definition of DLT. To this end, the NCI has developed a patient-reported outcomes version of CTCAE for use in clinical trials and is actively addressing the operational concerns to allow its full integration into clinical trials in collaboration with the US Food and Drug Administration and the Office for Human Research Protection.…”
Section: Discussionmentioning
confidence: 99%
“…The majority of gynecologic cancers were ovarian/fallopian tube/peritoneal cancers (n = 527 [77%]), which were followed by cervical cancer (n = 76 [11%]) and uterine cancer (n = 72 [11%]). The median number of lines of treatment before study enrollment for all patients was 4 (range, [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20].…”
Section: Patient Characteristicsmentioning
confidence: 99%